Effects of obesity on talar micro‐ and macro‐morphology. Issue 2 (27th January 2023) - Sylvester, Adam D.; Wescott, Daniel J.; Cunningham, Deborah L.; Gleiber, Devora S.
Abstract: The addition of information regarding obesity status to the forensic anthropological biological profile could significantly contribute to the identification of human skeletal remains since over 40% of the U.S. adult population is currently obese. This study examines the differences in talar shape and trabecular bone structure between obese and non‐obese individuals. A sample of 20 obese and 20 non‐obese divided evenly by sex was selected from the Texas State University Donated Skeletal Collection. Tali were imaged using x‐ray computed tomography (voxel size: 28–38.7 μm). Image stacks were processed to produce binary images as well as trabecular thickness and spacing maps. Landmark‐based geometric morphometric analyses were conducted to quantify shape variation. Shape coordinates were used to locate 100 geometrically homologous volumes of interest within each talus. Bone volume fraction, trabecular thickness, and trabecular spacing were extracted at each volume of interest. Within each sex, a one‐way ANCOVA was used to determine if significant differences exist between obese and non‐obese individuals in trabecular bone after controlling for age. The size of the talus as well as subtle aspects of shape were found to distinguish the sexes. The results further indicate that bone volume fraction significantly differs between obese and non‐obese males. In females, bone volume fraction is correlated with age but does not differ between obese and non‐obese. The study demonstrates that bone microstructure is a promising approach to estimating body mass or body mass index category but age effects diminish the potential for the talus to be used alone.